Experts to convene in Cairo for the “Consultation Workshop: Deep Diving into the Agritech Innovation Ecosystem in Egypt” - Zaccari, Claudia; Al-saffar, Reem (2024)
On 7 February 2024 at the InterContinental Cairo Semiramis, CGIAR Centers – Alliance of Bioversity International and CIAT, ICARDA, IWMI, IFPRI, and supported by the CGIAR Accelerate for Impact Platform (A4IP) – in collaboration with the Academy of Scientific Research and Technology of Egypt (ASRT) and under the auspices of the Ministry of Higher Education and Scientific Research of Egypt (MOHESR) hosted the "Consultation Workshop: Deep Diving into the Agri-tech Innovation Ecosystem in Egypt". Organized as part of CGIAR Regional Integrated Initiative Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA), this workshop convened 80 experts in agriculture and innovation for a multistakeholder dialogue about creating a conducive environment for testing, validating, and deploying agritech solutions to enhance the sustainability, resilience, and efficiency of agriculture in Egypt, all while boosting business competitiveness, attracting foreign investments, and empowering young talent. The feedback collected will support the design of the AgriTech4Egypt Innovation Challenge, to be launched in March 2024.